Humpback whales (Megaptera novaeangliae) continue migration after giving birth in temperate waters in Australia and New Zealand - McPhee-Frew, Jane; Dedden, Adelaide V.; Pirotta, Vanessa; Marshall, Andrew; Waples, Kelly; Raudino, Holly C.; Rogers, Tracey L. (Frontiers in Marine Science, 2025)
The spatial distribution of calving habitat of humpback whales (Megaptera novaeangliae) has been understood as confined to warm, low latitude waters. The need for females to reach such habitats to give birth and provide early maternal care underpins the dominant theories on humpback whale migration. In Australia, calving habitat is accepted to be distributed no further south than 23-28°S and is generally presumed not to occur in New Zealand. The aim of this study was to understand if humpback whales birth beyond these limits and, if so, whether cow-calf pairs continue migrating northward. Records of neonate calves were collated from several sources, including government agencies, annual migration surveys and opportunistic citizen science observations, primarily from tourism vessels. Strict inclusion protocols were applied to ensure correct identification of calves as neonates. More than 200 neonates were recorded in all jurisdictions in the study area, to 43°S, approximately 1300 – 1500 km south of the previously reported southern limit of calving grounds in Australasia. These records demonstrate that humpback whales do not confine their calving solely to tropical zones but exhibit a continuum of habitat use throughout their range. The cow-calf pairs were consistently observed to continue northward in Eastern Australia and New Zealand, suggesting that birth does not define the endpoint of the migration. There are management implications of these findings as currently some jurisdictions are not recognized as calving habitats. Therefore, the revision of protection measures in these areas given the new evidence of extended calving habitat would assist in reducing anthropogenic threats to young calves during vulnerable life stages. Additionally, the continuation of northward migration after birth of the calf is an important observation for migration theory. Future studies comparing the outcomes for calves born during migration with those born in the tropical wintering grounds could provide empirical information to evaluate hypotheses on the drivers of migration. The results of this study challenge prevailing notions of calving and migration behavior in this species.